Réponses

2014-02-27T00:10:16+01:00
Bonsoir,

a) E = 4x² + 8x - 5
Si x = 0,5, alors E = 4 * (0,5)² + 8 * 0,5 - 5
                           = 4 * 0,25 + 4 - 5
                           = 1 + 4 - 5
                           = 0

b) F = (2x + 2)² - 9

1) Développer et réduire F.
F = (2x + 2)² - 9
   = (4x² + 2 * 2x * 2 + 2²) - 9
   = 4x² + 8x + 4 - 9
   = 4x² + 8x - 5

2) Factoriser F

F = (2x + 2)² - 9
   = (2x + 2)² - 3²
   = [(2x + 2) - 3] [(2x + 2) + 3]
   = (2x + 2 - 3)(2x + 2 + 3)
   = (2x - 1)(2x + 5)

c) x = 0,5.

2x = 2 * 0,5
2x = 1
2x - 1 = 0

Donc F = 0 puisque F = (2x - 1)(2x + 5) et que le premier facteur du produit est nul ==> le produit F est nul.
2014-02-27T00:20:53+01:00
(a)
E = 4x² + 8x - 5

Pour x = 0.5 = 1/2

E = 4*(1/2)² + 8*1/2 - 5
E = 4*1/4 + 4 - 5
E = 1 + 4 - 5
E = 0 ( Zero )

(b)
 
(1) 
F = ( 2x + 2 )² - 9
F = ( 2x + 2 ) ( 2x + 2 ) - 9
F = 4x² + 4x + 4x + 4 - 9
F = 4x² + 8x - 5

(2)
F = (2x + 2)² - 9
F  = (2x + 2)² - 3²
F  = [(2x + 2) - 3] [(2x + 2) + 3]
F  = (2x + 2 - 3)(2x + 2 + 3)
F   = (2x - 1)(2x + 5)

(c)
 pour x = 0.5  ,,, F = 0 ,,,, car F = E